Topology optimization of micro-channel reactors using an improved multi-objective algorithm - Wang, Jiahao; Liu, Xiaomin; Wang, Yue (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
•Multi-physics model and multi-objective optimization algorithm are established.•The effect of outlet angles of MCR on optimal configurations is revealed.•Darcy friction term is modified using a polynomial function.•Strict volume constraints and pseudo-design domain concept are introduced.•The optimal configurations of NMCR and nNMCR are obtained. This study proposes an improved multi-objective density-based topology optimization (TO) model for Newtonian and non-Newtonian fluid micro-channel reactor(NMCR, nNMCR) to substantially improve the overall performance of MCR. Flow, catalytic reaction, and heat transfer in MCR under constant pressure driving is described by built a multi-physics model of continuous-flow exothermic reaction. TO adopts the material density as the design variable to control the changes in fluid and solid domains. The artificial Darcy friction improved by polynomial function is used to add the impermeability of intermediate density, and the Helmholtz partial differential filter and hyperbolic tangent projection are applied to eliminate the checkerboard phenomenon and structural ill-conditioning. The improved multi-objective algorithm based on the weighted-sum method and pseudo-design domain concept are proposed to avoid the local topological structure simplification and unreasonable. In examples, the effects of reactor geometries and outlet angles θ on optimal configurations and performance parameters of NMCR and nNMCR are investigated. Additionally, optimal solution set under multi-objective functions with different weight factors ω1 is solved, and Pareto frontier is established accordingly to reveal the trade-off relationship between the single-objectives. MCR responds to the proportion increase of flow single-objective in multi-objective function by homogenizing the local catalyst blocks distribution and increasing the flow channel length, thereby affecting the flow, diffusion and mixing. The local catalyst distributions of NMCR and nNMCR are significantly different due to different fluid properties. From the perspective of engineering, this study provides an efficient and applicable optimization method for designing MCR with higher comprehensive performance.